PENGEMBANGAN WEBSITE BANTU DIRI UNTUK MENGATASI KEDUKAAN PESERTA DIDIK SMA AKIBAT KEMATIAN ORANGTUA SECARA MENDADAK - Ulhaq, Aisyah Dhiya; Herdi, Herdi; Fitriyani, Hilma (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Adolescent grief due to the sudden death of parents has an impact on physical, social, emotional, psychological, and cognitive aspects. This study aims to develop a self-help website to overcome the grief of high school students due to the sudden death of one or both parents. Design Based Research is the method used in this research. DBR has three main stages namely; analysis and exploration, design and construction, and evaluation and reflection. The results of data collection obtained from the description of students' grief, media needs, and interventions that have been carried out by counseling teachers. The results showed that there were three grade 10 students suspected of experiencing prolonged grief and students' media needs. The second stage of website development is carried out which displays a menu, namely the homepage, pre-test, let's understand, self-help exercises, share stories, post-test, and contact. Stage three, testing was carried out by media experts with test results of 89% with a very feasible category, material test of 94% with a very feasible category, guidance & counseling practitioner test with test results of 100% and usability testing by users of 87% with a very feasible category. The final result of this research is a self-help website media to overcome the grief of high school students due to the sudden death of one or both parents.